Hydro power flexibility for power systems with variable renewable energy sources: an IEA Task 25 collaboration. Issue 1 (20th June 2016) - Huertas‐Hernando, Daniel; Farahmand, Hossein; Holttinen, Hannele; Kiviluoma, Juha; Rinne, Erkka; Söder, Lennart; Milligan, Michael; Ibanez, Eduardo; Martínez, Sergio Martín; Gomez‐Lazaro, Emilio; Estanqueiro, Ana; Rodrigues, Luis; et al.
Abstract : Hydro power is one of the most flexible sources of electricity production. Power systems with considerable amounts of flexible hydro power potentially offer easier integration of variable generation, e.g., wind and solar. However, there exist operational constraints to ensure mid‐/long‐term security of supply while keeping river flows and reservoirs levels within permitted limits. In order to properly assess the effective available hydro power flexibility and its value for storage, a detailed assessment of hydro power is essential. Due to the inherent uncertainty of the weather‐dependent hydrological cycle, regulation constraints on the hydro system, and uncertainty of internal load as well as variable generation (wind and solar), this assessment is complex. Hence, it requires proper modeling of all the underlying interactions between hydro power and the power system, with a large share of other variable renewables. A summary of existing experience of wind integration in hydro‐dominated power systems clearly points to strict simulation methodologies. Recommendations include requirements for techno‐economic models to correctly assess strategies for hydro power and pumped storage dispatch. These models are based not only on seasonal water inflow variations but also on variable generation, and all these are in time horizons from very short term up to multiple years, depending on the studied system. Another important recommendation is to include a geographically detailed description of hydro power systems, rivers' flows, and reservoirs as well as grid topology and congestion. WIREs Energy Environ 2017, 6:e220. doi: 10.1002/wene.220 This article is categorized under: Wind Power > Science and Materials Wind Power > Systems and Infrastructure Abstract :